Aplikasi Smartphone Menggunakan Fintech Dalam Transportasi Jakarta Untuk Belanja Dalam Online Shop - Mardika, Ersa Andhini; Pratama, Adrian Randy; Mu’azzi, Muhammad Naufal; Erick, Erick; Warnars, Harco Leslie Hendric Spits (KILAT, 2019)
We propose that smartphone applications with technology combine the market of lecture transportation when public passenger transportation must benefit from coupons on the market. The existence of several strategies based on the online application provided makes users still a little interested in that. The survey methodology is also used to collect data from customers by stratified random sampling between two different groups (users and non-users). This discovery highlights the importance of ease of use and usability in developing attitudes.